LONG-TERM DYNAMICS BETWEEN BITCOIN AND STOCK MARKETS - KOTVYTSKA, Nataliia; SHAROVA, Svitlana; SHCHERBATYKH, Denys (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This paper investigates the long-run relationship between Bitcoin and the S&P 500 index using daily price data from January 2018 to July 2024. While previous studies have focused primarily on correlation analysis and volatility spillovers, we employ both Engle-Granger and Johansen cointegration methodologies to examine the possibility of a long-run equilibrium relationship between these markets. Our results provide strong evidence of cointegration, with the Engle-Granger test indicating significance at the 5% level (p-value = 0.0288) and the Johansen trace statistics confirming one cointegrating relationship. Interestingly, this long-run relationship coexists with a relatively low daily return correlation (0.2884) and substantially different volatility profiles (Bitcoin: 68.56%, S&P 500: 19.87% annualized). These findings suggest that while Bitcoin and the S&P 500 may deviate substantially in the short term, they share common long-run drivers. Our results have important implications for portfolio diversification, statistical arbitrage strategies, and regulatory frameworks, challenging the conventional view of Bitcoin as a purely alternative asset class. The evidence of market integration supports the need for coordinated regulatory approaches and sophisticated risk management strategies in cryptocurrency investments.